Pengaruh Kualitas Layanan, Brand Ambassador Dan Electronic Word Of Mouth Terhadap Loyalitas Pelanggan Melalui Aplikasi Shopee - Hidayahtullah, Dwi Putri; Asteria, Beta (EKONOMI KEUANGAN DAN BISNIS, 2024)
E-commerce companies are increasingly emerging, making e-commerce compete in maintaining or even increasing customer loyalty. Therefore, this research was conducted to determine the perceptions of the people of the Special Region of Yogyakarta regarding the influence of service quality, brand ambassadors and electronic word of mouth and to determine their influence on customer loyalty. Where this research uses quantitative methods with associative problem formulation. The sample used in this research consisted of 100 respondents using a non-probability sampling technique to determine the sample on the condition that they had made repeat purchases on the Shopee application with a minimum age of 17 years who were domiciled in the Special Region of Yogyakarta. This research uses multiple linear regression data analysis which is processed using the SPSS version 26 application. Based on the data processing, the results show that service quality has an effect on customer loyalty, brand ambassadors have no significant effect on customer loyalty, and electronic word of mouth has a significant effect on customer loyalty. Therefore, service quality and electronic word of mouth need to be maintained and even improved because these variables have a significant influence on customer loyalty of Shopee application users.